A catalogue of Coleoptera specimens with potential forensic interest in the Goulandris Natural History Museum collection - Dimaki, Maria; Anagnou-Veroniki, Maria; Tylianakis, Jason (ENTOMOLOGIA HELLENICA, 2016)
This paper presents a catalogue of the Coleoptera specimens in the Goulandris Natural History Museum collection that have potential forensic interest. Forensic entomology can help to estimate the time elapsed since death by studying the necrophagous insects collected on a cadaver and its surroundings. In this paper forty eight species (369 specimens) are listed that belong to seven families: Silphidae (3 species), Staphylinidae (6 species), Histeridae (11 species), Anobiidae (4 species), Cleridae (6 species), Dermestidae (14 species), and Nitidulidae (4 species). The aim of this paper is to present this collection and its importance for studying forensic entomology.